Analisis Kesulitan Belajar dalam Menyelesaikan Masalah Teorema Phytagoras Kelas VIII Ditinjau dari Gaya Belajar - Luluk Ida Rahayu; Anwas Mashuri; Budi Sasomo (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
In teaching mathematics subjects, a teacher must be competent in designing innovative learning materials so that they can develop students' potential, which is expected to affect their learning outcomes and which is one of the influencing factors in student success in mathematics lessons is learning style. This study applies a descriptive method. The purpose is to describe the form of learning difficulties experienced by grade VIII students at MTs SA Al Murtadho Kedungwaru in learning mathematics on phytagoras theorem material referring to aspects of each student's learning style. In determining a subject in a study, it is carried out using the purpose sampling technique. There are three learning styles that will be studied further in this study, namely visual, auditorial, and kinesthetic learning styles. The research subjects of six students were taken representatives from a total of 34 students, in each class two representatives will be taken for those who have a visual learning style, two students also with an auditorial learning style, and two more students with a kinesthetic learning style. The techniques used to obtain the necessary data will be distributed questionnaires, test questions, interviews with students, and documentary evidence. This study applies two ways by comparing data from observation results with interview results and will also compare a person's assessment with various points of view with other people's perspectives. The results found in the study stated that there are difficulties in students including difficulties in understanding concepts, problems, and answering questions related to the Pythagorean theorem. So teachers need to find a learning style that is suitable for each student in order to help students understand the material so that students can solve the questions given appropriately.